Wildlife, livestock, and zoonotic threats: Advancing one health bio surveillance in Sabah, Malaysian Borneo - Vijay Kumar Subbiah; Azniza Mahyudin; Dexter Miller Robben (International Medical University, 2025)
The emergence of zoonotic diseases, or zoonoses, infections transmitted between animals and humans, is a growing global concern, particularly in ecologically diverse regions such as Borneo. Environmental changes, including habitat loss, climate variation, and increased human animal contact, often drive these diseases, leading to outbreaks that threaten both public health and biodiversity. In response, bio surveillance has become an essential tool for monitoring and managing these risks. Within the One Health framework, which emphasizes the interconnectedness of human, animal, and environmental health, bio surveillance involves the systematic tracking of diseases across sectors to enable early detection and timely response. Understanding how these risks manifest in regions like Borneo requires a closer look at its ecological history and the evolving pressures on its environment.